Implementation of the Duties and Functions of Supervisors of Islamic Religious Education at the Senior High School Level in Palembang City - Misnani Misnani; Kasinyo Harto; Saipul Annur (STAI Hubbulwathan Duri, 2023)
Supervisors play an important role in assisting and guiding teachers towards improving the quality of learning. This study aims to analyze the implementation of the duties and functions of supervisors of Islamic Religious Education in conducting academic supervision and the obstacles. The research method used is descriptive qualitative. The informants of this study were 4 supervisors at the high school level. Data were obtained through interviews, documentation, and observation. Data were analyzed through data reduction, data presentation, and conclusion. The results of this study indicate that the implementation of supervisory duties and functions is by Minister of Religion Regulation No. 2 of 2012, but the results have not been maximized due to various obstacles, including 1) the number of assisted schools; 2) the number of PAI teachers trained; 3) teacher preparation is not optimal; 4) lack of competence of supervisors; 5) lack of facilities; and 6) lack of supervisory, professional competency development activities.